Carbono almacenado en suelo y carbono en necromasa de árboles de Inga edulis “guaba” en varillal seco, Nina Rumi, Loreto-Perú, 2022 - Java Iberico, Alejandro Miguel (2024)
Disturbances or modifications in the use of the land in the dry forests of the Nina Rumi area can unbalance the ecosystem, generating alterations in the vegetal composition. On the other hand, a considerable portion of the total area of this rod forest has been used for various purposes, mainly migratory agriculture and the cultivation of fast-growing fruit species, such as Inga edulis. The general objective of this work is to quantify the carbon stored in soil and carbon in necromass of Inga edulis “guaba” trees of 2, 5 and 6 years in dry rods, Nina Rumi, Loreto, Peru, 2022. The methodology used in the field was to obtain 5 samples of necromass of 1 m2 and 5 pits of 30 cm * 30 cm * 30 cm deep under the Inga edulis trees and to determine the organic carbon was by the calcination method the values in t/ha /anus. The results revealed that the highest stored necromass was in 2-year-old Inga edulis trees with 7.47 t/ha/year. In addition, it was identified that the carbon stored in the necromass and soil was 3.735 t/ha/year. and 20,418 t/ha. respectively, The analysis of variance between soil carbon and necromass carbon using the Kruskal-Wallis test (p) = 0000, indicates that the difference is highly significant with a confidence level of 95% (p) = 0 .05, confirming the validity of the proposed hypothesis.